Análisis de equidad horizontal de las transferencias fiscales en el Perú - Samanamud Valderrama, Carlos Enrique (2017)
This article analyzes the horizontal equity of fiscal transfers in Peru. To this effect, the theoretical framework of fiscal transfers is presented first, followed by a description of the current classification of fiscal transfers in Peru according to the 2013 public budget. Similarly, a reclassification model of these transfers is developed to assess whether such distribution, from a horizontal equity perspective, would balance the necessity level of public goods and services in its jurisdiction with the transferred resources.